Exome‐wide single‐base substitutions in tissues and derived cell lines of the constitutive Fhit knockout mouse. Issue 4 (23rd February 2016) - Paisie, Carolyn A.; Schrock, Morgan S.; Karras, Jenna R.; Zhang, Jie; Miuma, Satoshi; Ouda, Iman M.; Waters, Catherine E.; Saldivar, Joshua C.; Druck, Teresa; Huebner, Kay
Abstract : Loss of expression of Fhit, a tumor suppressor and genome caretaker, occurs in preneoplastic lesions during development of many human cancers. Furthermore, Fhit‐deficient mouse models are exquisitely susceptible to carcinogen induction of cancers of the lung and forestomach. Due to absence of Fhit genome caretaker function, cultured cells and tissues of the constitutive Fhit knockout strain develop chromosome aneuploidy and allele copy number gains and losses and we hypothesized that Fhit‐deficient cells would also develop point mutations. On analysis of whole exome sequences of Fhit‐deficient tissues and cultured cells, we found 300 to >1000 single‐base substitutions associated with Fhit loss in the 2% of the genome included in exomes, relative to the C57Bl6 reference genome. The mutation signature is characterized by increased C>T and T>C mutations, similar to the "age at diagnosis" signature identified in human cancers. The Fhit‐deficiency mutation signature also resembles a C>T and T>C mutation signature reported for human papillary kidney cancers and a similar signature recently reported for esophageal and bladder cancers, cancers that are frequently Fhit deficient. The increase in T>C mutations in −/− exomes may be due to dNTP imbalance, particularly in thymidine triphosphate, resulting from decreased expression of thymidine kinase 1 in Fhit‐deficient cells. Fhit‐deficient kidney cells that survived in vitro dimethylbenz(a)anthracene treatment additionally showed increased T>A mutations, a signature generated by treatment with this carcinogen, suggesting that these T>A transversions may be evidence of carcinogen‐induced preneoplastic changes. Abstract : Due to absence of Fhit genome caretaker function, Fhit knockout mouse cells develop aneuploidy, allele copy number losses and −/− tissues develop >1000 single‐base substitutions in the 2% of the genome included in exomes. The mutation signature is characterized by increased C>T and T>C mutations, similar to the "age at diagnosis" signature identified in human cancers. The increase in T>C mutations in −/− exomes may be due to thymidine triphosphate imbalance, resulting from decreased expression of Thymidine Kinase 1 in Fhit‐deficient cells.